2012
DOI: 10.3390/md10040775
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Derived Polyunsaturated Aldehydes Do Not Structure the Planktonic Microbial Community in a Mesocosm Study

Abstract: Several marine and freshwater diatoms produce polyunsaturated aldehydes (PUA) in wound-activated processes. These metabolites are also released by intact diatom cells during algal blooms. Due to their activity in laboratory experiments, PUA are considered as potential mediators of diatom-bacteria interactions. Here, we tested the hypothesis that PUA mediate such processes in a close-to-field mesocosm experiment. Natural plankton communities enriched with Skeletonema marinoi strains that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
1
22
2
Order By: Relevance
“…In contrast to our 100 μM results, recent work by Paul et al (42) concluded that PUAs do not impact the structure of freeliving bacterial communities. However, these investigators examined the effects of individual PUAs at nanomolar concentrations, and it is possible that nanomolar concentrations simply do not affect community structure, whereas micromolar concentrations do.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to our 100 μM results, recent work by Paul et al (42) concluded that PUAs do not impact the structure of freeliving bacterial communities. However, these investigators examined the effects of individual PUAs at nanomolar concentrations, and it is possible that nanomolar concentrations simply do not affect community structure, whereas micromolar concentrations do.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to our 100 µM results, recent work by Paul et al concluded that PUAs do not impact the structure of free living bacterial communities (Paul and al, 2012). However, these investigators examined the effects of individual PUAs at nanomolar concentrations, and it is possible that nanomolar concentrations simply do not affect community structure, while micromolar concentrations do.…”
contrasting
confidence: 53%
“…Our H1 is hence rejected. Similarly, in a natural system, no significant changes in Chl were observed in PUA vs. control treatments (Paul et al 2012). Depending on the amount of PUA produced and released in the water, cells can develop resistance to successive exposure or undergo cell lysis (Vidoudez and Pohnert 2008).…”
Section: Microplankton Responsementioning
confidence: 97%